Suppression of impurity ions optical transitions dephasing in nanocrystals - Masalov, A.; Klochkov, V.; Maksimchuk, P.; Viagin, O.; Seminko, V.; Vazankov, D.; Malyukin, Yu. (Наноструктурное материаловедение, 2010)
Abnormally narrow spectral lines have been observed in the luminescence spectra of Y₂SiO₅Pr³⁺ and YVO₄:Eu³⁺ nanocrystals at the room temperature. This fact was interpreted as the result of optical transitions dephasing processes suppression in the nanocrystals. The general cause of the observed effect is the weakening of phonon scattering on the impurity centre as a result of the quantum size effect in nanocrystal phonon subsystem. At first the dependence of spectral line width on the nanocrystal size has been shown. Unnecessary of the deep cooling for narrow optical resonances obtaining makes these nanocrystals a potential candidate for the wide set of applications in the optical memory and quantum computing devices. На спектрах люмінесценції нанокристалів Y₂SiO₅Pr³⁺ та YVO₄:Eu³⁺ за кімнатної температури спостерігалася наявність аномально вузьких спектральних ліній. Це було інтерпретовано як результат заглушення процесів дефазування оптичних переходів у нанокристалах. Причиною зазначеного ефекту є ослаблення розсіювання фононів на домішковому центрі внаслідок впливу квантово-розмірного ефекту на підсистему фононів у нанокристалі. Уперше отримано залежність ширини спектральних ліній від розміру нанокристала. Відсутність потреби глибокого заморожування для отримання вузьких оптичних резонансів відкриває можливості використання таких нанокристалів для створення пристроїв оптичної памяті та квантових компютерів. На спектрах люминесценции нанокристаллов Y₂SiO₅Pr³⁺ и YVO₄:Eu³⁺ при комнатной температуре наблюдалось наличие аномально узких спектральных линий. Это было интерпретировано как результат подавления процессов дефазировки оптических переходов в нанокристаллах. Причиной наблюдаемого эффекта является ослабление рассеяния фононов на примесном центре в результате влияния квантово-размерного эффекта на подсистему фононов в нанокристалле. Впервые получена зависимость ширины спектральных линий от размера нанокристалла. Отсутствие необходимости глубокого замораживания для получения узких оптических резонансов открывает широкие возможности применения данных нанокристаллов для создания устройств оптической памяти и квантовых компьютеров.